Risk compensation in times of COVID-19: Do people keep distance when wearing a facemask? A rapid review - Gill A. Ten Hoor; Robert A. C. Ruiter; Gerjo Kok (Springer, 2024)
Abstract Aim To nuance the discussion on the suggested absence of the risk-compensation phenomenon in times of COVID-19. Subject and methods In many countries, behavioral restrictions for COVID-19 prevention started with asking people to stay 1.5 m away from each other. To further prevent the spread of the virus, governments made it mandatory for people to wear facemasks in situations where keeping the 1.5-m distance was not possible. This triggered a discussion among behavioral scientists regarding whether making face-masks mandatory might lead to the undesirable side effect that people would be less compliant with the 1.5-m distance rule: risk compensation. Mantzari et al. (2020) published a paper claiming that risk compensation was a non-existing phenomenon. Czyprionka et al. (2020) repeated the same claim, referring to the same original publications. We performed a rapid review of the existing literature and identified 19 papers that presented original data on studies that identified the consequences of wearing a facemask. Results The evidence for risk compensation is inconclusive. Risk compensation may occur with the encouraged use of face coverings. However, it may not always be present, especially when there are other social processes in play, such as respecting other people's choices. Conclusion Inconclusive evidence doesn't mean that risk compensation should be ignored or that potential public health interventions shouldn't be implemented. The introduction of mandatory face masks should, therefore, always be accompanied by a theory- and evidence-based health promotion campaign to prevent the possible negative effects of distancing. Carefully applying social psychological insights to guide people in their decision to wear masks when needed and to do so correctly, may overcome potential risk compensation and thereby optimize COVID-19 preventive efforts.